Comparative Analysis of Fixed Income Unit Trust Funds Versus Equity Unit Trust Funds in Malaysia - Aminah, Shari (2012)
This study examines the relationship between fixed income unit trust funds and equity unit trust funds for the period of January 2006 to October 2012. The performance of both types of funds are then compared to the market benchmark to determine whether they outperformed the market benchmark. The performance comparisons are made over several categories of equity sample namely overall equity, growth equity and value equity. The Kuala Lumpur Composite Index (KLCI) is used as the market benchmark for equity funds and fixed income funds with additional market benchmark of Maybank 12-month fixed deposit. A total of 31 fixed income funds and 57 overall equity funds which are made up of 37 growth equity and 20 value equity are evaluated by using three performance measures namely Treynor index, Sharpe index and Jensen index. The results indicate that the mean returns of equity funds are higher than the fixed income funds and market benchmark of KLCI. Nevertheless, when equity funds are compared against fixed income funds using Wilcoxon Signed Rank Test, Sharpe and Treynor ratios produce significant results. This means that the performance of fixed income funds varies from the performance of equity funds. However the Jensen index produces insignificant result. When the sample categorised into different equity types of funds, the finding shows a conflicting result. The Sharpe and Jensen ratios indicate insignificant results for growth equity funds sample. This means that the performance of fixed income funds is not different from that of equity funds in comparison to Treynor that shows a significant result. As for the value equity, Sharpe, Treynor and Jensen produce results that are significant. This means that the performance of fixed income funds varies from that of equity funds.